Contribución al estudio de la esclerosis sistemática progresiva (esclerodermia) - Silicani Della Pina, Armando (1973)
The present paper present our experience on thirty two patients with progresive sistemic sclerosis, both from the clinical andfrom the inmunological point of view; twelve of whom were treated with oral reserpine for a minimun period of six month. We found no significant correlation between the degree of severity of the disease and the inmunological studies that were performed. The most remarkable inmunoelectroforetic changes in the serum of these patients were moderate increased of the lgG, lgA, 2-M, G, lgM an A globulin types. In contrast what have been found by other authors, the antinuclear antibodies were just positive in (twelve oacients thirty seven percent in our serie); there was not a diagnostic pattern, and the speckel was the most frecuently found.  This disease must be considered a dfuse vascular one, which the most important lesion is at the microvascular level.Oral reserpine represents a hope in the treatment, when it is given early and for a long period of time.